Self-employment and well-being across institutional contexts - Michael Fritsch; Alina Sorgner; Michael Wyrwich (Friedrich Schiller University Jena, 2018)
This paper investigates whether the relationship between a person's occupational status and well-being differs across countries with varying institutional contexts. We find that the relationship between job- and life satisfaction of self-employed people as well as of paid employees varies considerably across countries. Our results indicate that entrepreneurship-friendly institutions in a country are conducive to the well-being of self-employed. Remarkably, the quality of entrepreneurial institutions also increases the levels of well-being of paid employees, but the effect is more pronounced for the self-employed.
Keywords: L26; I31; D01; D91; P51; 330; entrepreneurship; institutions; well-being; life satisfaction; job satisfaction